Special education leadership building effective programming in schools - Bateman, David 1963-; Cline, Jenifer L. (Routledge, 2019)
"Integrating coverage of the most important knowledge base, research, and practice in the field, this book prepares educators for the challenging role of special education leader. Special Education Leadership provides leaders with tools to, review programs, implement special education law, and build special education programs that effectively supervise and support teachers. Grounded in theory, this book also includes best practices for day-to-day operations, such as issues of teaching and learning, personnel selection and evaluation, basic financial management, working with parent relations, mental health issues, and legal matters related to special education. Full of advice from practitioners, end-of-chapter questions, and coverage of emerging trends, this book helps prepare special education administrators and supervisors to survive the pressures of working with students with disabilities while supporting appropriate services and preventing litigation"--Provided by publisher.